Differential gene expression profiles of human periodontal ligament cells preserved in Hank's balanced salt solution and milk. Issue 1 (17th June 2019) - Nam, Ok Hyung; Oh, Tae Jun; Lee, Jae‐Hyung; Hwang, Yu‐Shik; Choi, Sung Chul
Abstract: Background/Aim: Various types of storage media have been investigated to preserve avulsed teeth. However, the efficacies of storage media mainly focus on the aspect of cell viability. The aim of this study was to evaluate and compare the gene expression profiles of human periodontal ligament cells preserved in Hank's balanced salt solution (HBSS) and milk over different storage durations. Material and Methods: Human periodontal ligament cells were cultured and preserved in HBSS and milk for 3 and 6 hours. Next, total RNA was isolated. QuantSeq 3′ mRNA‐Sequencing was used to examine differences in gene expression in HBSS‐ and milk‐grown periodontal ligament cells. Bioinformatics analysis was also performed to predict the function of the differentially expressed genes. Results: The number of differentially expressed genes shared among all groups was 101. In gene set enrichment analysis, the shared differentially expressed genes in HBSS and milk were associated with the TNF‐α signaling pathway ( P = 1.07E −7 ). Seven hallmark gene sets were also identified in HBSS. Moreover, hallmark gene sets associated with hypoxia ( P = 7.26E −5 ) and apoptosis ( P = 4.06E −4 ) were identified in HBSS. In milk, 10 hallmark gene sets along with gene sets for inflammatory response ( P = 6.87E −3 ) were identified. Conclusions: Compared to those in milk, genes in HBSS were differentially expressed with increasing storage duration, suggesting that diverse and different gene expression may be involved in HBSS and milk. However, a more detailed functional analysis of these differentially expressed genes in storage solutions should be performed in the future.